2020
DOI: 10.3390/jcm9020294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Estimating Glomerular Filtration Rate with Three Different Equations among Older People. Preliminary Results of the Project “Screening for Chronic Kidney Disease among Older People across Europe (SCOPE)”

Abstract: We aimed at investigating to what extent CKD may be staged interchangeably by three different eGFR equations in older people, and evaluating the source of discrepancies among equations in a population of 2257 patients older than 75 years enrolled in a multicenter observational study. eGFR was calculated by CKD-EPI, BIS and FAS equations. Statistical analysis was carried out by Bland–Altman analysis. κ statistic was used to quantify the agreement between equations in classifying CKD stages. The impact of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…eGFR <60 mL/ min/1.73 m 2 compared to the CKD EPI equation. This is in line with results published by Tarantini et al on 7845 subjects older than 70 years, where BIS1 equation classified 20.1% subjects more to eGFR <60 mL/min/1.73 m 2 than CKD EPI equation 19 11,18,20 . Bland Altman analysis showed mean difference of 8.0 mL/min/1.73 m 2 being lower using BIS1 than CKD EPI (95% limits of agreement: +1.9 to -17.8).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…eGFR <60 mL/ min/1.73 m 2 compared to the CKD EPI equation. This is in line with results published by Tarantini et al on 7845 subjects older than 70 years, where BIS1 equation classified 20.1% subjects more to eGFR <60 mL/min/1.73 m 2 than CKD EPI equation 19 11,18,20 . Bland Altman analysis showed mean difference of 8.0 mL/min/1.73 m 2 being lower using BIS1 than CKD EPI (95% limits of agreement: +1.9 to -17.8).…”
Section: Discussionsupporting
confidence: 93%
“…found a systematic difference between equations, with the BIS1 mean difference of 8.9 mL/min/1.73 m 2 being lower than CKD EPI (95% limits of agreement: +3.4 to -21.3) 19 . Furthermore, multicentric observational study on 2257 subjects also reported lower mean difference of 8.97 mL/min/1.73 m 2 using BIS1 20 . Fan et al showed no superiority to CKD EPI equation compared with other equations (Japanese, BIS, and Caucasian and Asian pediatric and adult subjects (CAPA) equation) 21 .…”
Section: Discussionmentioning
confidence: 85%
“…An alternative explanation for the observed positive association between protein intake and SCr may reflect a better nutritional status and higher muscle mass percent in individuals with higher dietary protein intake. In contrast, elderly individuals with lower muscle mass might appear to have higher eGFR levels because of lower creatine and, consequently, creatinine production [40]. Also, specifically animal protein sources may contribute to a short-term increase in exogenous creatinine, resulting in higher total SCr and lower eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…As regards, potential sources of discrepancy among eGFR equations, serum creatinine, and muscle mass were recently reported to be relevant correlates of disagreement, also impacting known sex differences of the CKD-EPI and BIS or FAS equations ( 42 ). While muscle mass was not assessed in the present study, our findings add to current knowledge by showing that BUN may also be involved in determining differences among equations in a population of older NH residents.…”
Section: Discussionmentioning
confidence: 99%
“…We used a limited set of data in our study, and we cannot exclude that the study equations may be differently sensitive to not measured factors, such as hydration status and body composition. Indeed, sarcopenia is known to impact creatinine production, and muscle mass may affect differences among creatinine-based eGFR equations ( 49 ). Given that body composition was not assessed in our study, further comparative analysis including extended datasets in these kinds of patients seems desirable.…”
Section: Discussionmentioning
confidence: 99%